Pilot of primary care physician discussion and resource allocation after screening for unintentional injuries and social determinants of health - Sarah Denny; Mike Gittelman; Hayley Southworth; Samantha Anzeljc; Melissa Wervey Arnold (BMC, 2019)
Abstract Background Standardized screening tools used by pediatric providers can help determine a child's injury and social risks. This study determined if an office-based quality improvement program could increase targeted anticipatory guidance and community resource distribution to families. Methods Practices recruited from the Ohio Chapter, American Academy of Pediatrics' database self-selected to participate in a quality improvement project. Two age-appropriate screening tools, corresponding talking points and local resources for birth-1 year and 1-5 year aged children were developed for unintentional injury and social health determinant topics. After a one-day learning session, practice teams implemented the tools into well-child care visits for children < 5 years of age. Two months of retrospective baseline data was collected for each participating clinician. During the 6-month collaborative, physicians randomly reviewed 5 screening tools monthly for each age category to identify injury and social risk discussions and to determine if resources were provided. Frequencies of counseling and resource distribution were calculated. Participating providers received Maintenance of Certification IV credit. Results Ten practices (18 providers) participated and 667 tools (n = 313, birth-1 year, n = 354, 1-5 year) were collected. For birth-1 year, the most common risky behaviors were related to unintentional injuries: no CPR training 164(52%), car seat not checked 149(48%) and home furniture not secured 117 (37%). For 1-5 year screens, unintentional injuries were also most common: no CPR training 222(63%), car seat not checked 203(57%) and access to choking hazards 198(56%). Families practiced riskier behaviors for unintentional injuries compared to social risks for both age groups (birth - 1 year, social 189/4801 (4%) vs. unintentional injury questions 999/6260 (16%) and 1-5 years, social 271/5451 (5%) vs unintentional injury questions 1140/6372 (18%). From baseline, discussions increased from 31% to 83% for birth - 1 year and 24% to 86% for 1-5 year families. Resource distribution increased by 63% for birth-1 year and 69% for 1-5 year families by pilot conclusion. Conclusions Using standardized screening tools in an office setting shows that families often practice unintentional injury risks more than having social concerns. After screening, appropriate resources can be provided to families to encourage behavior change.